Effectiveness Study of Hybrid Caesar-Vigenere Cipher Method in Text Security - Wafha Zahra Mulqiya; Zulaeha; Vivie Zuliani Erikasari; Tyanshi Firli Maharani; Turmudi Zy, Ahmad (SISFOTENIKA, 2025)
Data security has become very important to protect data from threats such as theft and manipulation in this digital era. This research investigates how the hybrid Caesar-Vigenere Cipher method that combines Caesar Cipher and Vigenere Cipher algorithms protects text data with double encryption. This method uses the Three-Pass Protocol, which allows the sender and receiver to exchange messages without sharing keys, increasing the complexity of the ciphertext and improving the defense against brute force attacks. The results show that the hybrid algorithm improves the security of text data better than the single encryption method, especially for small to medium-sized applications. This research offers a practical solution to the problem of data security in the digital era.